Current etiology, clinical features and outcomes of bacteremia in older patients with solid tumors. Issue 2 (March 2019) - Antonio, Maite; Gudiol, Carlota; Royo-Cebrecos, Cristina; Grillo, Sara; Ardanuy, Carmen; Carratalà, Jordi
Abstract: Purpose: To assess the etiology, clinical features and outcomes of bacteremia in older patients with solid tumors. Methods: All episodes of bacteremia in hospitalized patients with solid tumors were prospectively collected. Patients aged ≥70 years were compared to patients aged <70 years. Risk factors for case-fatality rates in older patients were identified. Results: We compared 217 episodes of bacteremia involving older patients and 525 occurring in younger patients. Older patients had more frequently other comorbidities, but were less commonly neutropenic and carried less frequently central venous catheters. Bacteremia from an abdominal source was more common in patients ≥70, whereas an endogenous source and catheter-related infection were less frequently observed. Streptococcus bovis group (3.7% vs. 0.8%, p  = .01) and Listeria monocytogenes (4.6% vs. 1.9%, p  = .04) were more common in older patients, whereas coagulase-negative staphylococci were less frequently found (1.4% vs. 5.3% p  = .01). Infection due to multi-drug resistant (MDR) strains was significantly higher in older patients (17.1% vs. 10.9%, p  = .02), who in addition, presented higher overall mortality (35.4% vs 27.7%, p  = .04). In older patients, lung tumor, neutropenia, and low grade fever were associated with early mortality, whereas comorbidities, corticosteroids, septic shock and inadequate empirical antibiotic therapy were associated with overall mortality. Conclusions: We identified remarkable differences in the etiology and sources of bacteremia between older and younger cancer patients with bacteremia. Older patients had more frequent infection due to MDR organisms and presented a higher overall mortality. Corticosteroids and inadequate empirical antibiotic therapy are modifiable factors associated with mortality.